2020
DOI: 10.1038/s41419-020-03005-8
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between cardiomyocytes and noncardiomyocytes is essential to prevent cardiomyocyte apoptosis induced by proteasome inhibition

Abstract: Heart is a multi-cellular organ made up of various cell types interacting with each other. Cardiomyocytes may benefit or suffer from crosstalk with noncardiomyocytes in response to diverse kinds of cardiac stresses. Proteasome dysfunction is a common cardiac stress which causes cardiac proteotoxicity and contributes to cardiac diseases such as heart failure and myocardial infarction. The role of crosstalk between cardiomyocytes and noncardiomyocytes in defense of cardiac proteotoxicity remains unknown. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This finding suggests a crucial protective role for non-CM cells, such as CF, in order to promote CM survival after proteasome inhibition. Moreover, this study found that brain natriuretic peptide is released from CM upon proteasome inhibition, signaling other cardiac cells to prevent proteasome inhibitioninduced CM death via a paracrine function (Guo et al, 2020). The mechanisms responsible for this crosstalk between CM and other cardiac cells, such as CF, remain to be elucidated.…”
Section: New Perspectivesmentioning
confidence: 84%
“…This finding suggests a crucial protective role for non-CM cells, such as CF, in order to promote CM survival after proteasome inhibition. Moreover, this study found that brain natriuretic peptide is released from CM upon proteasome inhibition, signaling other cardiac cells to prevent proteasome inhibitioninduced CM death via a paracrine function (Guo et al, 2020). The mechanisms responsible for this crosstalk between CM and other cardiac cells, such as CF, remain to be elucidated.…”
Section: New Perspectivesmentioning
confidence: 84%
“…Lidocaine may inhibit the UPS by binding to the b5 subunit of the 20s proteasome in p53-postive cancer cells [148]. In any case, UPS inhibition can be linked to apoptosis [149][150][151][152]. Drugs that inhibit the catalytic activity of the UPS, including hallmark drugs like bortezomib and ixazomib [153] are used as chemotherapeutics as cancer cells have high rates of proteinturnover for survival [154].…”
Section: Discussionmentioning
confidence: 99%
“…Three cell culture containing different composition of cardiac cell types were performed as previously described [5]. Briefly, after decapitation, the ventricles of postnatal day 1 mouse pups were quickly dissected under a microscope.…”
Section: Cell Culture and Starvation Inductionmentioning
confidence: 99%
“…To determine the kinetics of starvation-induced autophagy in different cardiac cell types in vitro, we recruited a previously well-defined primary heterogeneous cell culture composed of four major cardiac cell types, including SAA+ cardiomyocytes, DDR2+ cardiac fibroblasts, SMA+ vascular smooth muscle cells and Lectin+ endothelial cells [5]. Autophagic activity was quantified by the number of LC3 puncta in each cell expressing corresponding cell type markers.…”
Section: Autophagic Activity Is Rapidly Declined In Nutrient-deprived...mentioning
confidence: 99%
See 1 more Smart Citation